Gender and ethnicity : married immigrants in Britain - Christian Dustmann; Francesca Fabbri (Center for Economic Studies and ifo Institute (CESifo), 2005)
In this paper we investigate the economic activity of married or cohabiting female immigrants in Britain. We distinguish between two immigrant groups: foreign-born females who belong to an ethnic minority group and their husbands, and foreign-born white females and their husbands. We compare these to native-born white women and their husbands. Our analysis deviates from the usual mean analysis and investigates employment, hours worked and earnings for males and females, as well as their combined family earnings, along the distribution of husbands? economic potential. We analyse the extent to which economic disadvantage may be reinforced at the household level and investigate to what extent it can be explained by differences in observable characteristics. We find that white female immigrants and their husbands have an overall advantage in earnings over white native born, both individually and at the household level. Minority immigrants do less well, in particular at the lower end of the husband's economic potential distribution. This is mainly due to the low employment of both genders, which leads to a disadvantage in earnings, intensified at the household level. Only part of this differential can be explained by observable characteristics.
Keywords: J15; 330; Frauenarbeitslohn; Lohndifferenzierung; Ethnische Gruppe; Haushaltseinkommen; Einkommensverteilung; Schätzung; Großbritannien